Design of bridges with skewed abutments for a target tolerable seismic loss. (1st June 2018) - Zakeri, Behzad; Zareian, Farzin
Highlights: A negative trend exists between bridge abutment skew angle and reliability index. The effect of abutment skew angle on reliability index is large at low repair costs. The reliability index decreases with increasing column height to diameter ratio. The proposed tool can be utilized to proportion bridge columns for target performance. Abstract: A comprehensive risk based bridge design procedure through which the effect of abutment skew angle is considered upfront aiming at uniformity in seismic risk is presented. We demonstrate a method for conceptual design of bridges with skewed abutments aiming at uniform performance (i.e., tolerable loss) objectives. In the proposed technique, few simple design aid graphs are developed by estimating the bridge repair cost ratios (RCRs) at different levels of column drift ratios (CDRs) and abutment skew angles. The suggested graphs parameters are estimated by implementing a full Monte Carlo probabilistic simulation over Pacific Earthquake Engineering Research Center (PEER) Probabilistic Based Seismic Assessment (PBSA). To show the significance of the proposed conceptual design method, a two-span Caltrans ordinary bridge class is selected for case study while various design parameters such as column diameter, column height to depth ratio, longitudinal reinforcement ratio, and span length are included as design variables. The effect of abutment skew angle on the probability of exceeding an RCR as well as probability of bridge collapse is explored by considering various bridge design parameters. Limitations of the proposed approach are discussed.